Sugarcane farming and the Great Barrier Reef: the role of a principled approach to change. (November 2018) - Deane, Felicity; Wilson, Clevo; Rowlings, David; Webb, Jeremy; Mitchell, Elaine; Hamman, Evan; Sheppard, Eva; Grace, Peter
Highlights: Regulation underpinned by relevant principles will ensure positive industry culture. Threshold requirements for a nutrient trading program to provide a good regulatory solution. A multifaceted regulatory approach will lead to best outcomes for regulators and for the industry. Abstract: Nutrient run-off from sugarcane farming practices has been identified as a significant threat to the Great Barrier Reef World Heritage Area (GBRWHA). The load of dissolved inorganic nitrogen (DIN) has increased dramatically in the last decades. This increase has been connected to poor water quality and outbreaks of Crown of Thorns starfish. It is suggested that the current level of the water quality is a failure that can be reversed by a focused regulatory response which meets the timeframe set by government. Considering the historical issues of regulatory capture, we argue that in devising effective regulation the culture of the sugar industry is of critical importance. Even though in theory it is possible for nutrient trading measures to achieve water quality targets, in the context of the regulation of DIN outfall produced by the sugarcane industry in the GBR catchment area, there are scientific and social barriers that work against such outcomes. We propose a combined instrument approach that involves both incentives and ultimately penalties to meet the timeframes considered necessary to protect the GBRWHA. Importantly such a strategy can be implemented without significant legislative changes.